Beyond Just Bacteria: Functional Biomes in the Gut Ecosystem Including Virome, Mycobiome, Archaeome and Helminths - Ravichandra Vemuri; Esaki M. Shankar; Marcello Chieppa; Rajaraman Eri; Kylie Kavanagh (Microorganisms, 2020)
Gut microbiota refers to a complex network of microbes, which exerts a marked influence on the host’s health. It is composed of bacteria, fungi, viruses, and helminths. Bacteria, or collectively, the bacteriome, comprises a significant proportion of the well-characterized microbiome. However, the other communities referred to as ‘dark matter’ of microbiomes such as viruses (virome), fungi (mycobiome), archaea (archaeome), and helminths have not been completely elucidated. Development of new and improved metagenomics methods has allowed the identification of complete genomes from the genetic material in the human gut, opening new perspectives on the understanding of the gut microbiome composition, their importance, and potential clinical applications. Here, we review the recent evidence on the viruses, fungi, archaea, and helminths found in the mammalian gut, detailing their interactions with the resident bacterial microbiota and the host, to explore the potential impact of the microbiome on host’s health. The role of fecal virome transplantations, pre-, pro-, and syn-biotic interventions in modulating the microbiome and their related concerns are also discussed.